The Impact of Labor Migration: The International Molders and Allied Workers Union in Canada, 1860-1885 - Williams, C. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1984)
This paper deals with some aspects in the relationships among Canadian molder locals, American molder locals and the binational organization.